Kecernaan Ransum Domba Berbasis Daun Sawit Teramoniasi yang Disuplementasi Sulfur, Fosfor, dan Daun Ubi Kayu - Nurhaita Nurhaita; J Jamarun; L Warly; M Zain (Faculty of Animal Science, Bogor Agricultural University, 2010)
This research aimed to evaluate the effect of S, P minerals and cassava leaves supplementation on utilization of ammoniated palm oil leaves in rumen sheep. The research used randomized block design with five rations as treatments and four groups as replication. The treatments were A= grass as control; B= ammoniated palm oil leaves; C= ammoniated palm oil leaves + 0.4% S and 0.27% P; D= ammoniated palm oil leaves + 5% cassava leaves; and E= ammoniated palm oil leaves +y 0.4% S, 0.27% P and 5% cassava leaves. The parameters measured were dry matter intake and digestibility of dry matter and fiber fraction (NDF, ADF, cellulose, and hemicelluloses). Dietary treatments had not significant effect on dry matter intake but significantly increased dry matter and fiber fraction digestibility, especially ADF. Diet E indicated the highest digestibility which supplied the entire nutrient required to growth and optimize activities of rumen microbes.